A research note: The informational benefits of CEO attendance-by-invitation at audit committee meetings. Issue 2 (August 2017) - Johnston, Joseph; Nowland, John
Abstract: This study contributes to the policy debate about independent audit committees by examining the occurrence and consequences of CEO attendance-by-invitation at audit committee meetings. We investigate whether this is a way for powerful CEOs to exert their influence over audit committee matters or an informal channel for information sharing between management and audit committees. We find that CEO attendance-by-invitation at audit committee meetings is positively related to firm complexity and firm governance practices, and is associated with lower earnings opacity. These results are consistent with CEO attendance-by-invitation at audit committee meetings enhancing information sharing between firm management and audit committees. Thus, this study identifies significant benefits from allowing CEOs to act as informal advisors at audit committee meetings.